The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1088/1742-5468/aceb55
|View full text |Cite
|
Sign up to set email alerts
|

Transverse-field XY spin chain with the competing long-range interactions: multi-criticality around the XX-symmetric point

Abstract: The transverse-field XY spin chain with competing antiferromagnetic long-range interactions, J r ∝ 1 / r α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Since the expression for the gap ∆(λ) is linear in λ, the critical exponent is zν = 1, independent of the σ value. Using the expression for the dispersion (312), the knowledge about λ c , and the definition of the dynamic critical exponent (314), Adelhardt et al [31] evaluated z and, therefore, also ν as a function of σ. The results of their calculations are presented in Figure 30.…”
Section: Isotropic Long-range Xy Chain In a Transverse Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the expression for the gap ∆(λ) is linear in λ, the critical exponent is zν = 1, independent of the σ value. Using the expression for the dispersion (312), the knowledge about λ c , and the definition of the dynamic critical exponent (314), Adelhardt et al [31] evaluated z and, therefore, also ν as a function of σ. The results of their calculations are presented in Figure 30.…”
Section: Isotropic Long-range Xy Chain In a Transverse Fieldmentioning
confidence: 99%
“…For β = 0, the critical exponents zν = 1 and critical values λ c = (2η(1 + σ)) −1 were determined analytically in Section 7.1, and it was shown that the universality class of the nearestneighbour isotropic chain remains for all σ > −1 [31]. A recent study [312] investigated the multicritical point using exact diagonalisation for comparably small system sizes. The critical points for β = 1/2 and β = 1/5 agree well with the exact limit and the pCUT+MC values.…”
Section: Antiferromagnetic Anisotropic Long-range Xy Chain In a Trans...mentioning
confidence: 99%